Antimicrobial and dna damaging activity of ochratoxin a extracted from Penicillium species - Vankudoth, Koteswara Rao; Sivadevuni, Girisham (International Journal of Pharma and Bio Sciences, 2014)
The present investigation was carried out by ten bacterial species, Bacillus subtilis, Escherishia coli, Enterobacter aerogenes, Klebsiella pneumoniae, Micrococcus luteus, Pseudomonas aeruginosa, Pseudomonas putida, Proteus mirabilis, Proteus vulgaris, Staphylococcus aureus and five fungal species, Aspergillus terreus, Penicillium aurantiogriseum, P.expansum, Paceliomycs varioti, Fusarium graminarium were screened for their sensitivity against ochratoxin A (OTA) produced by Penicillium verrucosum. Proteus mirabilis was highly sensitive followed by E.aureogens, B.subtilis and K. pneumoniae. Rest of the bacteria was intermediate in their sensitivity when compared with the streptomycin as standard. Similarly P.aurantiogriseum and Paeciolomyces varioti were comparatively more sensitive than the other fungi under study. Aspergillus terreus and P.expansum was sensitive to an intermediate extent. Simultaneously the DNA damaging activity of OTA was also evaluated by PRSET-B plasmid DNA treated with H2O2 plus different concentrations of OTA. The highest DNA stand breaks was observed on even at 25μg/ml of OTA and complete degradation of DNA stand breaks was observed on 30μg/ml of OTA.

Factors influence on growth, don and niv production by two species of fusarium isolated from finger millets [eleusine coracana l.] - Vankudoth, Koteswara Rao; Penugonda, Shilpa; Sivadevuni, Girisham; Reddy, S. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
ABSTRACT Objective: The present investigations (In vitro) on an influence of different synthetic and food based [flour] media, pH, temperature and microbial nutrients on growth, Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and F. culmorum was carried out. Methods: Fusarium species associated with the finger millets were isolated and identified phenotypically and further confirmed by molecular methods by Polymerase Chain Reaction [PCR]. Monosporic seven day old F. aethiopicum and F. culmorum were grown in CYA broth and incubated at 27±2°C on rotary shaker for 21 days at 120 rpm. At the end of 21 day incubation period, cultures were harvested for determination of fungal biomass. The resultant culture filtrates were extracted twice with ethyl acetate and concentrated to get and final concentration of 1 ml in methanol and employed for RP-HPLC analysis for detection of DON and NIV production. Results: Finger millets flour medium induced the highest amount of mycelial growth, DON and NIV production by F. aethiopicum. However, F. culmorum achieved highest amount of hyphal growth, DON and NIV production under the influence of yeast extract sucrose [YES] medium. Maize flour medium, rice flour medium and sorghum flour medium was next preffered substrates. Optimum pH of 5.5-6.5 and temperature of 20-35°C for growth, DON and NIV production was observed. Both the species of Fusarium failed to grow and produce toxins at pH 2.5-3.5 and temperature of 40°C. Yeast extract was most favorable for maximum DON and NIV production, which increased with an increase in its concentration. On the other hand, malt extract and beef extract induced good growth and mycotoxin production at comparatively higher concentration in both the species of Fusarium under study. Conclusion: Comparatively food based media were the better substrates than synthetic media for both growth and DOIN and NIV production by two species of Fusarium under investigation. A positive correlation coefficient [r] on growth [0.458], DON [0.744] and NIV [0.882] was recorded among the media and both the species of Fusarium. Keywords: Finger millets, F. aethiopicum, F. culmorum, Synthetic media, pH, Temperature, Microbial nutrients, DON, NIV, HPLC

Influence of different species of Penicillium and their culture filtrates on seed germination and seedling growth of sorghum - Vankudoth, Koteswara Rao (Journal of Biochemical Technology, 2014)
The present investigations influence of Penicillium species and their culture filtrates on the seed germination and seedling growth of sorghum was studied. Culture filtrate of P. nordicum, P. verrucosum, P. chrysogenum, P. commune, P. citrinum, P.camemberti and P. digitatum were comparatively more toxic and significantly inhibited the seed germination and seedling growth varied with the species. However, pathogenicity of different inoculum of Penicillium species also exhibited varying seedling growth inhibition with P. citrinum, P. chrysogenum, P. commune, P. italicum, P. verrucosum and P. expansum assayed by water agar method. A significant phytotoxicity of these species inhibited coleoptile 32-70%, radicle 10-87% and leaf growth 20-86% with correlation coefficient 0.65, 0.67 and 0.79%, and were observed respectively. In-vitro mycotoxin production was assayed by culture filtrates of major mycotoxigenic strains revealed production of ochratoxin A (OTA), cyclopiazonic acid (CPA), rubratoxin B (RTB), griseofulvin (GRI), citrinin (CIT), patulin (PAT), penitrem A (PENA) and mycophenolic acid (MPA) screened by TLC/HPLC. Toxicity of species of Penicillium on seed germination, coleoptile, radicle, and leaf elongation inhibition may be attributed to the toxin-chemotypes produced by the species of Penicillium. However, even non-toxigenic strains of Penicillium also caused mild inhibition which may be attributed to the presence of other toxin-chemotypes.

Efficacy of food preservatives and volatile compounds in the control of ochratoxin a production by penicillium species - Vankudoth, Koteswara Rao; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, S. M. (Proceedings of the National Academy of Sciences, India - Section B: Biological Sciences, 2015)
In the present investigation different volatile compounds and food preservatives were tested for their efficiency in the control of growth and ochratoxin A (OTA) production by Penicillium verrucosum and Penicillium nordicum. Volatiles such as phenols and formic acid which have no residual effect were proved to be effective in checking the growth and OTA production by both the species of Penicillium under study. Vapours of phenols and formic acid significantly inhibited OTA produced by P. verrucosum, while aniline and toluene inhibited the OTA production by P. nordicum to a significant level. A positive correlation coefficient was observed between the growth and toxin production by P. verrucosum (0.55) and P. nordicum (0.66) against different volatile compounds tried. Among food preservatives, sodium acetate and sodium metabisulphate were responsible for total inhibition of OTA production by P. verrucosum at 150 lg/ml concentration. P. nordicum proved to be comparatively more resistant to these substances than P. verrucosum. In conclusion of present investigation, phenol, formic acid, amyl alcohol, propionic acid, sodium acetate and sodium metabisulphate were found to be effective in checking the growth and OTA production by both the species of Penicillium under investigation, and can be exploited in protecting the poultry feed from unwanted mould growth and mycotoxin production.

Culture conditions for the production of thermostable lipase by thermomyces lanuginosus - Sreelatha, B.; Vankudoth, Koteswara Rao; Kumar, R. Ranjith; Girisham, Sivadevuni; Reddy, S. M. (Journal of Basic and Applied Sciences, 2016)
In the present investigation lipase production by three strains of thermophilic Thermomyces lanuginosus (GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14) was carried out in submerged fermentation process. Olive oil and triacetin (0.1%) were added to the basal medium, which stimulated the lipase production. The maximum lipase was produced by GSLMBKU-10 and GSLMBKU-13 in yeast extract starch medium supplemented with triacetin (0.1%). The optimum pH was recorded at 6.0, 6.5 and 7.0 by GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14 respectively. T. lanuginosus GSLMBKU-10 strains failed to produce lipase at pH 8.0. The optimum temperature for lipase production was observed at 45 °C by GSLMBKU-14 and GSLMBKU-10, while that for GSLMBKU-13 was at 50 °C. The marginal temperature ranged from 45 °C to 50 °C for both lipase production and vegetative growth by the three strains of T. lanuginosus under study. In conclusion, the GSLMBKU-13 strain was comparatively superior in the production of lipase than the other two strains under investigation.

Taxonomy of mycotoxigenic fungi - Vankudoth, Koteswara Rao; Sivadevuni, Girisham; Reddy S. M. (Scientific Publisher, 2016)
Mycotoxins, toxic metabolites of molds elaborated during their colonization of foods and feeds, pose a threat to human and animal life. Molds are the diverse group of fungi, which grow in compatatively dry and warm environments, produce copious amount of spores and promote the elaboration of these mycotoxins. Mycotoxigenic fungi, which are unique their sporulating apparatus and exhibit wide variation in their morphology, poses a challenge in their identification. There are numerous examples of their misidentification leading to wrong conclusions. Precise information on taxonomy of these fungi is lacking. Therefore, this book fulfills the need of providing comprehensive information and keys helpful for the accurate identification of these moulds. The book also provides comprehensive account of morphology, mycotoxins produced and factors leading to the elaboration of mycotoxins. Information on their molecular detection, anamorphic and teleomorphic relationships is also included.

Microbial synthesis of mammalian metabolites of spironolactone by thermophilic fungus thermomyces lanuginosus - Sreelatha, B.; Prasad, G. Shyam; Vankudoth, Koteswara Rao; Sivadevuni, Girisham (Steroids, 2018)
Mesophilic fungi are well recognized as models of mammalian drug metabolism. Thermophilic fungi remained unexplored despite having a unique mechanism of growing at higher temperatures and performing wide diverse reactions. The present investigation is directed to isolate a promising thermophilic fungal strain capable of biotransformation using spironolactone as a model drug. Two-stage fermentation protocol was followed for the process. The transformation of spironolactone was identified by HPLC and structure elucidation of the metabolites was done with the help of LC-MS/MS analysis and previous reports. A strain of Thermomyces lanuginosus isolated from decomposed banana peel waste was found to be most promising in transforming spironolactone to 4 metabolites viz.7α-thiospironolactone (M1) canrenone (M2), 7α-thiomethylspironolactone (M3) and 6β-OH-7α-thiomethylspironolactone (M4), the major mammalian metabolites reported previously. The synthesis of metabolites of spironolactone by T.lanuginosus similar to mammals clearly states that this fungus possess enzyme system similar to mammals. Hence, this fungus has the potential to use as a model organism for studying drug metabolism.

Structural insight into a membrane intrinsic Acyltransferase from Chlorobium tepidum - Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar (Current Microbiology, 2019)
The Lipid A component of the outer membrane of Gram-negative bacteria is an integral part of the permeability barrier known as LPS, which actively prevents the uptake of bactericidal compounds. It is clinically very significant, as it is known to elicit a strong immune response in the humans, through the TLR4 complex. The Lipid A species are synthesized through a highly conserved multistep biosynthetic pathway. The final step is catalyzed by acyltransferases of the HtrB/MsbB family, which are members of a superfamily of enzymes, present in all domains of life with important roles to play in various biological processes. The investigation of a putative dual functioning enzyme which can add both laurate and myristate residues to the (Kdo)(2)-lipid IVA (precursor of Lipid A) would give a snapshot into the versatility of substrates that these enzymes catalyze. In this study we have cloned and purified to homogeneity, such a putative dual functional acyltransferase from Chlorobium tepidum, and attempted to study the enzyme in more details in terms of its sequence and structural aspects, as it lacks conserved residues with other enzymes of the same family.